The Effectiveness of Using Blended Learning in Mathematics Teaching on Algebra (Jurusan Matematika FMIPA UNNES, 2020)
Currently the use of blended learning activities is many used. Even now in high school blended learning has been applied to several subjects. One of the subjects that utilizes blended learning is mathematics. One of mathematics materials in high school is algebra that can utilize blended learning in the delivery of its material. Algebra is one material where most students get low grades. In this paper we will discuss the effectiveness of using blended learning in algebra material high school. The present study is designed to answer the question. We can find the effectiveness of using blended learning. The research field (statistical population) included all available digital and written sources related to the blended learning. The research sample was a purposeful homogeneous sample. It is used to describe the sample that includes information based on the qualitative and the quantitative research goals. This study reviews the literature and provides a scientific background by reviewing some of the contributions made by various researchers and institutions to the concept of blended learning. The results showed that students who used blended learning in algebra learning got better results compared to students who used traditional learning methods.